Liquid viscosity of low-GWP refrigerant mixtures (R32 + R1234yf) and (R125 + R1234yf). (October 2015) - Dang, Yagu; Kamiaka, Takumi; Dang, Chaobin; Hihara, Eiji
Abstract : Graphical abstract: Highlights: We measured liquid viscosity of low GWP refrigerant R1234yf binary mixtures. Viscosity of R1234yf mixtures were correlated with the roughness hard-sphere method. Viscosity of R1234yf mixtures were correlated with the Grunberg and Nissan method. Abstract: In this work, the viscosity of R1234yf, (R32 + R1234yf), and (R125 + R1234yf) in one-phase liquid was measured. The combined expanded uncertainty of viscosity measurement apparatus of confidence of 0.95 ( k  = 2) is about 2.0%. The measurements of mixtures containing (30.0, 50.0, and 70.0) wt% R32 or R125 were carried out between T  = (283.0 and 323.0) K (at intervals of T  = 5 K) and P  = (1.58 and 2.74) MPa, with a moving piston viscometer (VISCOpro 1600, accuracy ±1.0%) and a Coriolis flowmeter (Ultramass MKII, accuracy ±0.001 g/ml). The measured data were correlated with a hard-sphere (RSH) method and the Grunberg and Nissan method. The average absolute deviations are (2.2 and 3.3)% for the (R32 + R1234yf) and (R125 + R1234yf) mixtures by RSH method, (2.8 and 1.3)% for the (R32 + R1234yf) and (R125 + R1234yf) mixtures by Grunberg and Nissan method, while (3.5 and 2.4)% for the (R32 + R1234yf) and (R125 + R1234yf) mixtures by RefProp V9.1, respectively.